Analysis of policies and initiatives for climate change mitigation in South Africa - Nsubuga, F.W.N. (Francis Wasswa Nkugwa) (University of Pretoria, 2022)
Mini Dissertation (MSc (Environmental Management))--University of Pretoria, 2022.